1993
DOI: 10.1152/ajpheart.1993.265.5.h1571
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate enhances recovery of rat hearts after ischemia and reperfusion by preventing free radical generation

Abstract: Pyruvate protects myocardium from ischemic and anoxic injury, effects that have been attributed to beneficial metabolic alterations. Pyruvate also reacts with hydrogen peroxide in vitro, and pyruvate prevents free radical injury in other organs. Hearts supplied with 2 mM of pyruvate with glucose during reperfusion recovered significantly more mechanical function (81%) than those provided with 2 mM of acetate (which does not react with free radicals) and glucose (49%) or glucose alone (27%). Pyruvate significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…Involvement of PHD inhibition for lactate-induced HIF-1a and HIF-2a stabilization does not exclude additional effects of lactate on the cellular redox status, as lactate oxidation to pyruvate (the lactate dehydrogenase 1 reaction) increases the NADH/NAD C ratio and pyruvate has antioxidant properties. 49,50 Considering that cancer cells chronically adapted to extracellular acidity activate HIF-2a and become addicted to glutamine, 51 the contribution of protons cotransported with lactate by MCT1 certainly deserves further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of PHD inhibition for lactate-induced HIF-1a and HIF-2a stabilization does not exclude additional effects of lactate on the cellular redox status, as lactate oxidation to pyruvate (the lactate dehydrogenase 1 reaction) increases the NADH/NAD C ratio and pyruvate has antioxidant properties. 49,50 Considering that cancer cells chronically adapted to extracellular acidity activate HIF-2a and become addicted to glutamine, 51 the contribution of protons cotransported with lactate by MCT1 certainly deserves further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Salahudeen et al (39) reported that intravenous infusion of sodium pyruvate protects rats from renal parenchymal injury induced by injecting H 2 O 2 into the renal artery. After the publication of that paper, a number of other investigators reported that treatment with pyruvate could protect animals from the deleterious effects of a variety of conditions thought to be mediated by ROS, including myocardial I/R (4,7,8,11,35), intestinal I/R (6), and HS/R (30).…”
Section: Discussionmentioning
confidence: 99%
“…REACTIVE SPECIES OF OXYGEN (ROS) have been implicated as being important mediators in a variety of pathological conditions, including burns (20), various forms of ischemia-reperfusion (I/R) injury (8,15,16,26), and hemorrhagic shock (9,10,17,32 Pyruvate, a key intermediate in cellular metabolism, is an effective scavenger of ROS. In a reaction characteristic of ␣-keto carboxylic acids in general, pyruvic acid (the simplest member of this class of compounds) rapidly undergoes nonenzymatic decarboxylation in the presence of H 2 O 2 to form acetate, carbon dioxide, and water (5,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the effect of various free radical scavengers on PTP opening has been investigated in different models of ischemia/reperfusion. Pyruvate may protect the heart against ischemia/reperfusion due to its free radical scavenging activity although it is also a good fuel for oxidative phosphorylation which, unlike glucose, does not require ATP-dependent activation before oxidation [156,157]. Indeed, in the Langendorff-perfused rat heart it was demonstrated directly that addition of pyruvate to the perfusion medium before the onset of ischemia significantly inhibited PTP opening which was associated with a greater recovery of cardiac function [77].…”
Section: Inhibition Of Ptp Opening By Free Radical Scavengersmentioning
confidence: 99%